EPIDEMIOLOGY OF LYMPHATIC FILARIASIS IN ADO-ODO /OTA LOCAL GOVERNMENT AREA OF OGUN STATE, NIGERIA. (2013)
Lymphatic filariasis, caused by Wuchereria bancrofti is a public health problem with high morbidity. The Global Progamme for Elimination of Lymphatic Filariasis has targeted its eradication by 2020. Available information showed that the disease is endemic in Ogun State, Nigeria. However, Ado-Odo/Ota Local Government Area has never been part of any known intervention for control of the disease despite the reported cases in the area. This study was conducted to assess the prevalence of lymphatic filariasis in Ado-Odo/Ota LGA and provide information critical for the launching of a reliable control programme in the area. Five hundred volunteers (442 adults and 58 children) were recruited according to WHO standard between April, 2008 and November, 2009 from a clinic set up in the local government health centre. Finger-prick blood sampling for parasitological examination was carried out at night between 10pm and 2am. Thick blood films were made for species identification and microfilariaemia. Gross examination of participants for clinical manifestation of the disease was graded using WHO method. Chronic involvements of the male genitalia were graded as hydrocele stage I-IV (increasing sizes of true hydrocele). Affected limbs in males and females were graded as stages I (early pitting oedema), II (non-pitting oedema with thicken skin and loss of elasticity), III (evident elephantiasis with deep skinfolds and/or warty lesions). Pre-tested and structured questionnaire was used to obtain demographic information and assess knowledge, attitude and practice of the participants in the management of the disease. Data were analysed using Chi square and Student’s t-test at p= 0.05. Wuchereria bancrofti microfilaraemia was prevalent among the subjects examined with a total of 105 (21.0%) participants infected. The highest prevalence of infection 35(30.7%) was recorded among those within the stratified age group of 60-69 years in both sexes. Prevalence of infection increased with age and was higher in males 61(27.1%) than in females 44(16.0%). The youngest male and female infected were 9 and 10 years respectively. Intensity of infection was not gender or age dependent. Microfilaria geometric mean intensities ranged from 18.3 - 33.4 mf/mL of blood and were highest in adults in the stratified age group of 70-79 years (33.4mf/mL of blood). True hydrocele occurred in 38(16.9%) males aged 9-70 years old with stage 1V being the most abundant (36.8%). Stages 1-111 limb elephantiasis was found in 7(3.1%) males and 16(5.8%) females while 14(5.1%) females had elephantiasis of the breast. Clinical signs increased with age. Most participants 398(79.6%) thought the disease was caused by spiritual attack, 477(95.4%) thought that it was not transmissible 356(71.1%) had been stigmatized while 387(77.4%) were of the opinion that the disease was curable by traditional healers. Prevalence was also significantly higher in farmers and the unemployed while the use of bed nets did not significantly reduce infection. There was high prevalence and intensity of lymphatic filariasis in Ado-Odo/Ota local government area of Ogun State. There is a need for appropriate intervention strategies in the area.